2018
DOI: 10.1073/pnas.1716771115
|View full text |Cite
|
Sign up to set email alerts
|

Defining the sizes of airborne particles that mediate influenza transmission in ferrets

Abstract: SignificanceEmerging respiratory pathogens pose significant public health threats as a result of their potential for rapid global spread via multiple non-mutually exclusive modes of transmission. The relative significance of contact, droplet, and airborne transmission for many respiratory pathogens remains a knowledge gap, and better understanding is essential for developing evidence-based measures for effective infection control. Here, we describe and evaluate a transmission chamber that separates virus-laden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 38 publications
10
86
0
Order By: Relevance
“…The results of this study imply that replication in the URT of ferrets, and more specifically the nasal respiratory epithelium, is important for the generation and expulsion of influenza virusladen particles from donor ferrets. As particles expelled from the URT are thought to be bigger than those expelled from the LRT, the results of this study could imply that transmission of IAVs between ferret is mediated by respiratory droplets rather than aerosols, which is in accordance with the studies by Zhou et al 39 and Gustin et al 40 . Zhou et al 39 showed that naive or influenzainoculated ferrets exhaled a greater number of fine particles (<1.5 µm) than large particles but that viral RNA was predominantly present in particles > 4 µm.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study imply that replication in the URT of ferrets, and more specifically the nasal respiratory epithelium, is important for the generation and expulsion of influenza virusladen particles from donor ferrets. As particles expelled from the URT are thought to be bigger than those expelled from the LRT, the results of this study could imply that transmission of IAVs between ferret is mediated by respiratory droplets rather than aerosols, which is in accordance with the studies by Zhou et al 39 and Gustin et al 40 . Zhou et al 39 showed that naive or influenzainoculated ferrets exhaled a greater number of fine particles (<1.5 µm) than large particles but that viral RNA was predominantly present in particles > 4 µm.…”
Section: Discussionsupporting
confidence: 92%
“…The agent of COVID-19 (SARS-CoV-2) can be detected in various clinical samples such as saliva, sputum, stool, and blood using polymerase chain reaction [1]. However, as World Health Organization stressed repeatedly 1 , 2 current scientific data suggest that SARS-CoV2 is transmitted via respiratory droplets and contact [2]. The droplets are respiratory particles which are larger than 5 μm in diameter and can travel, at the maximum, 6 feet (1.83 m) through the air before landing [2].…”
Section: Transmissionmentioning
confidence: 99%
“…However, as World Health Organization stressed repeatedly 1 , 2 current scientific data suggest that SARS-CoV2 is transmitted via respiratory droplets and contact [2]. The droplets are respiratory particles which are larger than 5 μm in diameter and can travel, at the maximum, 6 feet (1.83 m) through the air before landing [2]. There is no clinical evidence that blood or bodily fluids pose a risk for transmission [3] To recall this solid data is very important while choosing personal protective equipment.…”
Section: Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was still a knowledge gap of gene-modified bacteria in the trace of airborne microorganism. Aerosolization of bacteria, which was susceptible to the suspending medium and shear stress, was widely performed in lab-experiment such as air sterilization and air infection [47][48][49][50][51][52][53][54][55]. Aerosolization and gene modification of bacteria could be jointly used for tracing airborne microorganism.…”
Section: Introductionmentioning
confidence: 99%